Prevention strategies for parasitic infections - LOZNEANU, Irina (One Health & Risk Management, 2021)
Introduction. A parasite is an organism that lives in or on another organism (the host) and benefits (for example, by deriving nutrients) at the host’s expense. Parasitic diseases exert a pronounced biological diversity and an increased ability to adapt to new environmental conditions Therefore, it points to a widespread of parasitic infections among the population of the world, which is a global public health problem. The relevance of parasitic diseases is due to their high share among infectious diseases. According to WHO, more than 1 billion people are estimated to be infected with various species of intestinal parasites, whereas according to official statistics based on national reports, helminthiasis is also widespread in the Republic of Moldova. Material and methods. To describe and measure the phenomenon, an analysis of scientific literature sources, as well as Google Academic, Pubmed and ECDC databases was carried out. Results. Most parasitic infections are often linked to areas with inadequate sanitation. Fecal-oral transmission is a common way to acquire a parasite. A parasitic infection is suspected in people who have typical symptoms and who live in or have travelled to an area where sanitation is poor. The intensification of international relations and population migration over the recent years poses a threat on importing parasitic diseases from the other countries. According to literature sources, there is a consensus within the research community that parasitosis remains undiagnosed in many patients. Thus, it determines the most vulnerable population, mainly affecting the children’s health. Laboratory analysis of specimens, including special tests to identify proteins released by the parasite (antigen testing) or their genetic material (DNA) have been described in the studied literature for diagnosing parasitic infections. Based on data analysis of literature sources, growth proliferation of parasitic infections is probably due to the inadequate system of diagnosis and epidemiological surveillance. Therefore, healthcare system is currently lacking strategies regarding the prevention of parasitic diseases such as cost-effective preventive measures, which lead to unjustified expenses. Some studies emphasize the great importance of cultural and health level of the population while complying with prevention measures. Recent research shows the innovative role of various prevention strategies used in the health systems elsewhere in the European region. These involve a multidimensional approach to improving health, including the development and implementation of policies and legislation; early detection of patients with parasitic diseases, followed by their isolation and treatment; promoting educational activities and raising public awareness of the health programs. Conclusions. Parasitic diseases are the most common human parasitic diseases. In addition to the health effects of the population, parasites are directly or indirectly associated to socioeconomic decline. Parasitic diseases are accompanied by new emerging risks and require an increased attention and promotion of preventive measures.